Geometric feature descriptor and dissimilarity-based registration of remotely sensed imagery - Kahaki S.M.M.; Arshad H.; Nordin M.J.; Waidah Ismail (Public Library of Science, 2024)
Indexed by WOS/SCOPUS/ERA